2019
DOI: 10.5194/aab-62-171-2019
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation (CNV) in the <i>IGF1R</i> gene across four cattle breeds and its association with economic traits

Abstract: The insulin-like growth factor 1 receptor (IGF1R) plays a vital role in immunomodulation and muscle and bone growth. The copy number variation (CNV) is believed to the reason for many complex phenotypic variations. In this paper, we statistically analyzed the copy number and the expression profiling in different tissue types of the IGF1R gene using the 422 samples from four Chinese beef cattle breeds, and the mRNA of IGF1R was widely expressed in nine tissue types of adult cattle (heart, liver, kidney, muscle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…The knockout mice experiment suggested the positive impact of HMGA2 expression on myoblast growth [ 32 ]. On the other hand, Chinese beef cattles with copy number loss of IGF1R had significantly better growth trait such as body weight, body height and hucklebone width [ 33 ]. In addition, HMGA2 and IGF1R were strongly associated with size differences between dog breeds [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockout mice experiment suggested the positive impact of HMGA2 expression on myoblast growth [ 32 ]. On the other hand, Chinese beef cattles with copy number loss of IGF1R had significantly better growth trait such as body weight, body height and hucklebone width [ 33 ]. In addition, HMGA2 and IGF1R were strongly associated with size differences between dog breeds [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with SNP, CNVs are longer fragments of variation with more significant effects on the growth traits of sheep. More and more copy number variation studies have been performed on different species, such as human [24], mouse [25], cattle [26,27], chicken [28], monkey [29], and sheep [30,31]. In recent years, with increasing consumer requirements for sheep quality and the development of molecular breeding, there is a need to exploit CNV molecular genetic variation for economic trait selection and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of IGF1R gene in muscle was found through bovine muscle transcriptome sequencing in the early stage of the laboratory, and bioinformatics analysis was conducted on it by animal quantitative trait loci (QTL) Database and NCBI. The previous study found the mRNA of IGF1R was widely expressed in heart, liver, kidney, muscle, fat, stomach, spleen and lung (from female cattle) and testis (from male cattle) in adult cattle, with the highest level of expression in testis and the middle-level expression in muscle (Ma et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%